PELATIHAN PEMBUATAN HANDSANITIZER BERSAMA POSYANDU REMAJA DESA GEDANGAN KABUPATEN SUKOHARJO - Hutapea, Henny Parida; Ambarwati, Septiana (Jurnal Abdimas Musi Charitas, 2024)
Antiseptic liquid or nowadays often called hand sanitizer is a hand antiseptic product whose use is very easy and practical. This product has become popular and is often used by people since the Covid 19 pandemic to kill bacteria without using water. It can be used anytime and anywhere, for example after touching things, before eating, after going to the toilet, after shopping, after throwing away the trash. Community empowerment activities in training on making hand sanitizer were carried out at the Gedangan Village Hall. The aim of this community service activity from the Industrial Chemistry Study Program at the Polsapa Surakarta is to convey information and knowledge and provide skills to members of the Gedangan Grogol Sukoharjo Village Youth Posyandu in making hand sanitizer that is safe to use. This activity was attended by 43 participants using the lecture method regarding material on making hand sanitizers and direct manufacturing practices by the activity implementing team. Next, practical workshop activities for participants who are divided into 3 groups. From the results of this community service activity, it can be concluded that the understanding and skills of the Gedangan Gorogol Sukoharjo Village Youth Posyandu regarding the material and practice of making hand sanitizers have increased. This is demonstrated by the ability to respond to questions from the activity implementation team during the activity from the start to the end of the activity and being able to make your own hand sanitizer.